Scleral exposure influences social judgments of trustworthiness, attractiveness, sociability, and social rank in White faces - Mathias Boyer-Brosseau; Simon Rigoulot; Sébastien Hétu (PLoS ONE, 2026)
Faces are powerful sources of social information, and the eye region plays a central role in shaping first impressions. While prior studies have suggested that scleral exposure may influence social judgments, findings remain inconsistent, and experimental approaches, nonexistent. The present study employed a controlled experimental design to explore how scleral exposure might influence judgments of trustworthiness, attractiveness, sociability, and perceived social rank in peer-related facial perception. A total of 162 participants rated 50 neutral faces twice, each digitally manipulated to display small and large scleral exposure. Results showed a consistent “scleral exposure effect”: across all measured social judgments, faces with larger scleral exposure were rated more favorably than the same faces with smaller scleral exposure. No interactions emerged between scleral exposure and sex of the raters or sex of the presented faces, indicating that these scleral exposure effects may reflect general sex-independent mechanisms. These findings provide the first experimental evidence that scleral exposure shapes multiple dimensions of social judgment, favoring greater exposure.